Potensi Gambut Tropika Sebagai Sumber Energi - Bostang Radjagukguk (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1986)
There are large expanses of as yet untapped peat resources in the tropics potentially utilizable energy source. Indonesia has by far the largest occurrence estimated at 8.8 million hectares with peat thickness of greater than 2 m. The energy related characteristics of tropical peat appear not to differ substantially from those of sphagnum peat of the northern latitude countries in which peat has long been utilized for energy. are now several possible forms of peat product designed for practical use in electrical, heat, and steam generating plants, in industry, and in household application. Prospect of peat as an alternative source of energy in tropical countries, particularly in Indonesia appear promising. In the short term prospect of application in Indonesia would appear to be restricted to local use for small size generating plants and for household use. In the long term however, the possibility of Indonesian peat as an exportable commodity should not be ruled out. The possibility and potential of using the Indonesian peat and peatlands for various purposes including energy, call for an intersectoral coordination and cooperation in exploration and exploitation. Development of peat for agricultural, forestry, energy, and recreational uses can be complementary